Wear-resistant porcelain tile with silver sand effect on surface and preparation method of wear-resistant porcelain tile
By applying silver sand surface glaze and silver sand metal dried glaze on the surface of the ceramic brick brick, and achieved the effect of silver sand from weak to strong, it is difficult to adapt to low temperature and fast burns in the existing technology. The problem of poor abrasion resistance of the system and the black gold sand throwing glaze has achieved high decoration performance and good wear resistance.
Patent Information
- Application Number
- CN202411476790.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-22
AI Technical Summary
Among the existing architectural ceramics, the artistic glaze of daily use porcelain is difficult to adapt to the low-temperature fast firing system of architectural ceramics, and the black gold sand glaze is applied with high glaze and poor wear resistance.
A method of preparing wear-resistant porcelain tiles with a silver sand effect on the surface is adopted, which includes applying a silver sand glaze and a silver sand metal dry grain glaze on the surface of the bricks, and firing them at a maximum firing temperature of 1180°C to 1200°C. Achieve the silver sand effect from weak to strong.
The overall silver metal luster effect on the surface of the tile is achieved, the decoration performance of the product is improved, and the production cost is reduced. It has good wear resistance and pollution resistance.
Smart Images

Figure CN119330752A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of building ceramics, and in particular to a wear-resistant porcelain tile with a silver sand effect on the surface and a preparation method thereof. Background Art
[0002] With the development of the architectural ceramics market, there are more and more types of architectural decoration materials, and consumers have higher requirements for tile materials, pattern levels, colors, and decorative effects. The artistic glaze of daily-use porcelain is very popular among consumers because of its unique artistic style. Many manufacturers have begun to apply the artistic glaze of daily-use porcelain to architectural ceramics. However, since the artistic glaze of daily-use porcelain needs a long time of heat preservation to crystallize, it is difficult to adapt to the low-temperature fast firing system of architectural ceramics.
[0003] Chinese patent CN2017111166511.0 discloses a glaze imitating black gold sand marble effect and its application. The glaze imitating black gold sand marble effect is composed of sand crystal protective glaze, mica iron oxide, ceramic printing paste, and polishing glaze. Through mica iron oxide, sand crystal protective glaze, and black gold sand polishing glaze, a better gold sand effect is presented on the ceramic tile. However, the glaze amount of the black gold sand polishing glaze is 1.5 to 2.5 times that of ordinary polishing glaze, and good transparency is required to present the gold sand effect. Therefore, the black gold sand polishing glaze will have a large amount of glass phase after firing, which makes the wear resistance of the glaze after polishing extremely poor, and a large amount of ferric oxide will also reduce the wear resistance of the glaze. Summary of the invention
[0004] In view of the above problems, the present invention provides a wear-resistant porcelain tile with a silver sand effect on the surface and a preparation method thereof. After firing, a silver sand effect from weak to strong will be generated on the surface of the tile. This decorative effect is different from the flash products on the market that are only partially embellished. The overall surface of the wear-resistant porcelain tile has a silver metallic luster from weak to strong, giving people a stunning visual effect and improving the decorative performance of the product. Moreover, the preparation method of the present invention does not require inkjet printing, saving the cost of inkjet printing equipment and ink, greatly reducing the production cost, simplifying the production process, and achieving a technological breakthrough.
[0005] In a first aspect, the present invention provides a method for preparing a wear-resistant porcelain tile having a silver sand effect on the surface. The preparation method comprises the following steps: Apply silver sand glaze on the surface of the brick; Applying silver sand metal dry granular glaze on the surface of the brick after applying the silver sand surface glaze; The brick blanks applied with the silver sand metal dry granular glaze are fired and polished to obtain wear-resistant porcelain tiles with a silver sand effect on the surface.
[0006] Preferably, the mineral composition of the silver sand metal dry particle glaze includes flaky mica iron oxide and silver sand metal dry particles; wherein the mass ratio of flaky mica iron oxide to silver sand metal dry particles is (5-10):(90-95).
[0007] Preferably, the chemical composition of the silver sand metal dry particles includes: by mass percentage, ignition loss: 0.5% to 0.8%; Al 2 O 3 :14.2%~18.5%;SiO 2 :40.1%~49.3%;Fe 2 O 3 : 10.4% ~ 19.6%; CaO: 1.2% ~ 4.3%; MgO: 0.05% ~ 0.5%; K 2 O: 1.2%~4.4%; Na 2 O: 1.6%~3.8%; TiO 2 :2.5%~4.5%; ZnO: 2.4%~4.8%; P 2 O 5 :7.2%~14.2%;Li 2 O: 1.4%~3.6%; CaF 2 :2.1%~4.3%.
[0008] Preferably, the aspect ratio of the flaky mica iron oxide is 65-110.
[0009] Preferably, the chemical composition of the silver sand metal dry particle glaze includes: by mass percentage, burning loss: 0.6% to 1.0%; Al 2 O 3 :12.3%~16.2%;SiO 2 :36.2%~46.6%;Fe 2 O 3 : 15.7% ~ 25.9%; CaO: 1.2% ~ 3.6%; MgO: 0.05% ~ 0.5%; K 2 O: 1.4%~3.2%; Na 2 O: 1.3%~2.8%; TiO 2 :1.9%~4.1%; ZnO: 2.1%~4.2%; P 2 O 5 :6.5%~12.5%;Li 2 O: 1.2%~3.4%; CaF 2 :1.8%~3.9%.
[0010] Preferably, the silver sand metal dry granular glaze is applied by pouring glaze; preferably, the specific gravity of the silver sand metal dry granular glaze is 1.30-1.34 g / cm3 , glaze application amount is 750~860g / m 2 .
[0011] Preferably, the mineral composition of the silver sand metal dry particles includes, by mass percentage, 20% to 30% potassium feldspar, 10% to 20% washed kaolin, 20% to 30% quartz, 20% to 40% iron phosphate, 5% to 10% fluorite, 4% to 10% zinc oxide, 6% to 8% spodumene, and 4% to 6% rutile.
[0012] Preferably, the mineral composition of the silver sand glaze includes zirconium-free glaze and cobalt black material, wherein the mass ratio of the zirconium-free glaze to the cobalt black material is 100:(2-5).
[0013] Preferably, the chemical composition of the zirconium-free glaze includes: by mass percentage, loss on burning: 1.2% to 1.8%; SiO 2 :56.4%~60.6%;Al 2 O 3 :28.2%~32.3%; CaO: 0.6%~0.9%; MgO: 0.3%~0.5%; K 2 O: 3.1%~5.2%; Na 2 O: 3.2% to 4.8%; Preferably, the mineral composition of the zirconium-free glaze includes, by mass percentage, 35% to 45% potassium feldspar, 0.1% to 5% sodium feldspar, 20% to 35% nepheline, 8% to 12% washed kaolin, 5% to 10% quartz, and 15% to 20% calcined alumina.
[0014] Preferably, the chemical composition of the silver sand glaze includes: by mass percentage, burning loss: 1.4% to 2.2%; SiO 2 :55.4%~62.3%;Al 2 O 3 :27.8%~31.5%; CaO: 0.6%~1.0%; MgO: 0.2%~0.4%; K 2 O: 3.2%~5.7%; Na 2 O: 3.2% to 5.8%; CoO: 2.5% to 4%.
[0015] Preferably, the silver sand glaze is applied by pouring glaze; preferably, the specific gravity of the silver sand glaze is 1.82-1.86 g / cm 3 , glaze application amount is 600~700g / m 2 .
[0016] Preferably, the maximum firing temperature is 1180-1200° C., and the firing time is 40-50 minutes.
[0017] In a second aspect, the present invention provides a wear-resistant porcelain tile with a silver sand effect on the surface. The wear-resistant porcelain tile with a silver sand effect on the surface is obtained according to the preparation method. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a brick surface effect diagram of the porcelain brick of Example 1; Figure 2 It is a brick surface effect diagram of the porcelain tile of Example 2. DETAILED DESCRIPTION
[0019] The present invention is further described by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention. Unless otherwise specified, each percentage refers to the percentage by mass. The following is an exemplary description of the preparation method of the wear-resistant porcelain tile with silver sand effect on the surface of the present invention.
[0020] The green body powder is pressed into shape to obtain a brick. The green body powder commonly used in the art can be used. As an example, the chemical composition of the green body powder includes: in terms of mass percentage, ignition loss: 3.7% to 4.5%; SiO 2 :67.8%~69.5%;Al 2 O 3 :17.2%~19.6%;Fe 2 O 3 :0.5%~0.8%;TiO 2 :0.1%~0.3%; CaO: 0.4%~0.7%; MgO: 0.3%~0.8%; K 2 O: 2.8%~3.9%; Na 2 O: 2.2%~2.8%.
[0021] The green body can be prepared by using ceramic raw materials commonly used in the art. The green body raw materials are ball-milled, powder-sprayed and granulated, and pressed to obtain a brick green body. The powder can be applied in the mold cavity of the press for pressing. The moisture content of the green body powder is preferably controlled at 7.0wt% to 7.6wt%. As an example, the particle size of the green body powder includes: in terms of mass percentage, 20 mesh sieve residue <2%, 40 mesh sieve residue 30% to 40%, 60 mesh sieve residue 75% to 85%, 100 mesh sieve residue > 92%, and the sieve residues of each mesh number are cumulative values.
[0022] Dry the bricks. The bricks can be dried in a drying kiln. The moisture content of the bricks after drying is preferably controlled within 0.2wt% to 0.3wt%.
[0023] Apply silver sand glaze on the surface of the brick to form a glaze layer. The dried brick surface can be cleaned before applying the silver sand glaze.
[0024] The mineral composition of the silver sand glaze includes zirconium-free glaze and cobalt black material. Among them, the mass ratio of zirconium-free glaze and cobalt black material is 100: (2-5). The silver sand glaze adopts a combination of zirconium-free glaze and cobalt black material, which can make the glaze surface appear gray-black after firing. The subsequent silver sand metal dry particle glaze applied on the silver sand glaze is like a silver light in the black sky, which plays a role in improving the silver sand effect on the surface. Moreover, the zirconium-containing glaze has a high whiteness, poor silver sand effect, and will also increase costs.
[0025] The chemical composition of the zirconium-free glaze includes: by mass percentage, burning loss: 1.2% to 1.8%; SiO 2 :56.4%~60.6%;Al 2 O 3 :28.2%~32.3%; CaO: 0.6%~0.9%; MgO: 0.3%~0.5%; K 2 O: 3.1%~5.2%; Na 2 O: 3.2%~4.8%.
[0026] As an example, the mineral composition of the zirconium-free glaze includes, by mass percentage, 35% to 45% potassium feldspar, 0% to 5% (preferably 0.1% to 5%) sodium feldspar, 20% to 35% nepheline, 8% to 12% washed kaolin, 5% to 10% quartz, and 15% to 20% calcined alumina.
[0027] In some technical solutions, the chemical composition of the silver sand glaze may include: by mass percentage, burning loss: 1.4% to 2.2%; SiO 2 :55.4%~62.3%;Al 2 O 3 :27.8%~31.5%; CaO: 0.6%~1.0%; MgO: 0.2%~0.4%; K 2 O: 3.2%~5.7%; Na 2 O: 3.2% to 5.8%; CoO: 2.5% to 4%.
[0028] Water and auxiliary materials can be added to the mineral composition of the silver sand glaze to adjust the required specific gravity. The auxiliary materials include sodium tripolyphosphate and sodium carboxymethyl cellulose. Among them, sodium carboxymethyl cellulose can account for 0.1wt% to 0.4wt% of the mineral composition of the silver sand glaze, and sodium tripolyphosphate can account for 0.1wt% to 0.4wt% of the mineral composition of the silver sand glaze. In actual production, water can be added to the glaze slurry of the silver sand glaze to adjust the required specific gravity of the glaze.
[0029] The silver sand glaze can be applied by pouring glaze. Preferably, the specific gravity of the silver sand glaze is 1.82-1.86 g / cm 3 , glaze application amount is 600~700g / m2 The glazing parameters of the silver sand glaze are controlled within this range, which can cover the prickly heat on the surface of the blank and is also conducive to controlling the brick shape.
[0030] The bricks with silver sand glaze are dried. This can dry out the moisture of the glaze layer as much as possible. Electric kiln drying can be used. For example, the drying temperature is 250-280°C and the drying time is 120-240 seconds.
[0031] Silver sand metal dry granule glaze is applied to the surface of the tile blank after the silver sand glaze is applied. The mineral composition of the silver sand metal dry granule glaze includes flaky mica iron oxide and silver sand metal dry granules. The flaky mica iron oxide itself has a strong silver metallic luster. After the silver sand metal dry granules are fired, crystals with a silver metallic luster will precipitate and have a relatively weak metallic luster. The two are matched with each other, so that the silver metallic luster on the surface of the tile changes from weak to strong, from strong to weak, and they complement each other, giving people a stunning visual sense. Among them, the mass ratio of flaky mica iron oxide and silver sand metal glaze is (5-10): (90-95). The content of flaky mica iron oxide is too low, so that the silver sand effect on the surface is weak. The content of flaky mica iron oxide is too high. Although the silver sand effect on the surface is strong, the production cost is too high. If only mica iron oxide is used, the glaze can only achieve a flashing effect, and the full metallic luster effect cannot be achieved.
[0032] Preferably, the aspect ratio of the flaky mica iron oxide is 65 to 110. If granular mica iron oxide with a small aspect ratio is used, the silver metallic luster is weak and a large amount of mica iron oxide needs to be added. However, the main component of mica iron oxide is α-Fe 2 O 3 , which belongs to flux, and excessive mica iron oxide will produce a large amount of glass phase, which will reduce the wear resistance of the tile surface. The present invention adopts flaky mica iron oxide with a large diameter-to-thickness ratio, which has a strong silver metallic luster, and adding a small amount can meet the demand. Therefore, using flaky mica iron oxide to replace granular mica iron oxide can improve the silver sand effect of the glaze on the one hand, and on the other hand, it does not affect the wear resistance of the glaze.
[0033] In some technical solutions, the chemical composition of the silver sand metal dry particles includes: by mass percentage, ignition loss: 0.5% to 0.8%; Al 2 O 3 :14.2%~18.5%;SiO 2 :40.1%~49.3%;Fe 2 O 3 : 10.4% ~ 19.6%; CaO: 1.2% ~ 4.3%; MgO: 0.05% ~ 0.5%; K 2 O: 1.2%~4.4%; Na 2 O: 1.6%~3.8%; TiO 2: 2.5%~4.5%; ZnO 2.4%~4.8%; P 2 O 5 :7.2%~14.2%;Li 2 O: 1.4%~3.6%; CaF 2 : 2.1% to 4.3%. Among them, TiO 2 , ZnO is a crystallization agent, Li 2 O、CaF 2 It is a flux and can also promote crystallization, causing a large amount of Fe to precipitate on the surface. 2 O 3 and crystalline iron-aluminum spinel, which makes the glaze surface have metallic luster after firing and also improves the wear resistance of the glaze surface. 2 O 3 It is introduced by nano corundum to further improve the wear resistance of the glaze.
[0034] As an example, the mineral composition of the silver sand metal dry particles includes, by mass percentage, 20% to 30% potassium feldspar, 10% to 20% washed kaolin, 20% to 30% quartz, 20% to 40% iron phosphate, 5% to 10% fluorite, 4% to 10% zinc oxide, 6% to 8% spodumene, and 4% to 6% rutile.
[0035] If the mineral composition of flaky mica iron oxide and silver sand metal dry particles are directly mixed and used, the glaze surface will be almost entirely glass phase after firing, with poor wear resistance and no granular texture on the surface.
[0036] In some technical solutions, the chemical composition of the silver sand metal dry particle glaze includes: by mass percentage, burning loss: 0.6% to 1.0%; Al 2 O 3 :12.3%~16.2%;SiO 2 :36.2%~46.6%;Fe 2 O 3 : 15.7% ~ 25.9%; CaO: 1.2% ~ 3.6%; MgO: 0.05% ~ 0.5%; K 2 O: 1.4%~3.2%; Na 2 O: 1.3%~2.8%; TiO 2 :1.9%~4.1%; ZnO: 2.1%~4.2%; P 2 O 5 :6.5%~12.5%;Li 2 O: 1.2%~3.4%; CaF 2:1.8%~3.9%. The chemical composition of the silver sand metal dry particle glaze refers to the chemical composition of the mineral material of the silver sand metal dry particle glaze, that is, the chemical composition of other raw materials (specifically mica iron oxide and silver sand metal dry particles) excluding auxiliary materials.
[0037] A glaze slurry of silver sand metal dry particles glaze is prepared. In addition to the flaky mica iron oxide and the silver sand metal dry particles, the glaze slurry also includes auxiliary materials (suspending agents) accounting for 210wt% to 220wt% of the silver sand metal dry particles. As an example, the auxiliary materials include: by weight, 30 to 40 parts of sodium carboxymethyl cellulose, 16 to 27 parts of glycerol, 20 to 30 parts of ethylene glycol, 3 to 5 parts of preservatives, and 20 to 30 parts of water.
[0038] The silver sand metal dry granular glaze can be applied by pouring glaze. Preferably, the specific gravity of the silver sand metal dry granular glaze is 1.30-1.34 g / cm 3 , glaze application amount is 750~860g / m 2 . The specific gravity of the silver sand metal dry granular glaze within this range is conducive to the uniformity of glazing. If the specific gravity of the silver sand metal dry granular glaze is too low, the glaze curtain is easy to float, resulting in bell-shaped defects; if the specific gravity is too high, bubbles are easy to appear, resulting in glaze pit defects. If the amount of silver sand metal dry granular glaze applied is too small, the glaze surface is difficult to crystallize, resulting in weak silver sand effect on the surface of the prepared porcelain tile samples; if the amount of silver sand metal dry granular glaze applied is too much, the prepared porcelain tile samples will be too turtle-shaped, exceeding the standard, and also increasing the production cost.
[0039] If silver sand dry particles and transparent polished glaze are mixed together, a large amount of glaze is needed to achieve the gold sand effect with high transparency. After firing, the glaze surface has a large amount of glass phase and many pores, and the wear resistance of the glaze surface after polishing is extremely poor.
[0040] Firing. Put it into the kiln for firing. The highest firing temperature is 1180℃~1200℃, and the firing time is 40 minutes to 50 minutes. If the firing temperature is too low, although the surface of the porcelain tile has a silver sand effect, the surface is rough and the pollution resistance is poor; if the firing temperature is too high, the silver sand metal dry particles cannot be crystallized, resulting in a poor surface silver sand effect.
[0041] Polishing. Preferably fine brushing. As an example, the arrangement of the fine brushing grinding blocks is 5 groups of grinding brushes.
[0042] Edging and packing.
[0043] The preparation method of the wear-resistant porcelain tile with silver sand effect on the surface of the present invention produces a silver sand effect from weak to strong on the surface of the tile after firing. This decorative effect is different from the flashing products on the market that are only partially embellished. The entire surface of the silver sand porcelain tile has a silver metallic luster from weak to strong, giving people a stunning visual effect and improving the decorative performance of the product. The wear resistance level of the wear-resistant porcelain tile with silver sand effect on the surface of the present invention is level 4, 6000 revolutions; the pollution resistance is level 5; the silver sand glaze gloss after firing is 4 to 8 degrees. In addition, due to the coloring of the surface glaze and the self-coloring effects of the silver sand metal dry particles and the flaky mica iron oxide, the present invention does not require inkjet printing after applying the silver sand surface glaze, which saves the cost of purchasing inkjet printing equipment and ink for production, and greatly reduces the production cost.
[0044] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0045] The anti-pollution performance is tested in accordance with the test standard GB / T 3810.14-2016.
[0046] The wear resistance performance is tested according to the test standard GB / T 3810.7-2016.
[0047] Example 1
[0048] The preparation method of the wear-resistant porcelain tile with silver sand effect on the surface comprises the following steps:
[0049] Step 1: Press the green body powder into shape to obtain a brick.
[0050] Step 2. Apply silver sand glaze on the surface of the dried brick. The mineral composition of the silver sand glaze includes zirconium-free glaze and cobalt black material, wherein the mass ratio of zirconium-free glaze to cobalt black material is 100:3. The chemical composition of the zirconium-free glaze includes: by mass percentage, loss on ignition: 1.8%; SiO 2 :58.2%;Al 2 O 3 :30.8%; CaO: 0.8%; MgO: 0.3%; K 2 O: 3.8%; Na 2O: 4.3%. The mineral composition of the zirconium-free glaze includes: by mass percentage, potassium feldspar 40%, sodium feldspar 5%, nepheline 25%, washed kaolin 9%, quartz 5%, calcined alumina 16%. The chemical composition of the silver sand glaze includes: by mass percentage, ignition loss: 1.8%; SiO 2 :56.6%;Al 2 O 3 :29.8%; CaO: 0.8%; MgO: 0.3%; K 2 O: 3.3%; Na 2 O: 4.6%; CoO: 2.8%. The silver sand glaze is applied by pouring glaze, with a specific gravity of 1.84g / cm 3 , glaze application amount is 650g / m 2 .
[0051] Step 3. Apply silver sand metal dry granule glaze on the surface of the brick after applying silver sand silver sand surface glaze. The mineral composition of the silver sand metal dry granule glaze includes flaky mica iron oxide and silver sand metal dry granules, wherein the mass ratio of flaky mica iron oxide to silver sand metal dry granules is 5:95. The chemical composition of the flaky mica iron oxide includes: by mass percentage, Fe 2 O 3 :99.45%;SiO 2 :0.55%. The diameter-to-thickness ratio of the flaky mica iron oxide is 80. The chemical composition of the silver sand metal dry particles includes: by mass percentage, ignition loss: 0.6%; Al 2 O 3 :14.2%;SiO 2 :41.3%;Fe 2 O 3 :16.8%; CaO: 2.4%; MgO: 0.2%; K 2 O: 3.1%; Na 2 O: 2.4%; TiO 2 :3.2%;ZnO:2.8%;P 2 O 5 :7.8%;Li 2 O: 2.5%; CaF 2 :2.7%. The mineral composition of the silver sand metal dry particles includes: by mass percentage, potassium feldspar 20%, washed kaolin 10%, quartz 20%, iron phosphate 30%, fluorite 6%, zinc oxide 4%, spodumene 6%, rutile 4%. The chemical composition of the silver sand metal dry particle glaze includes: by mass percentage, ignition loss: 0.7%; Al 2 O 3 :13.5%;SiO 2 :39.3%;Fe 2 O 3:20.9%; CaO: 2.3%; MgO: 0.2%; K 2 O: 2.9%; Na 2 O: 2.3%; TiO 2 :3.0%;ZnO:2.6%;P 2 O 5 :7.4%;Li 2 O: 2.4%; CaF 2 :2.5%. Silver sand metal dry granular glaze is applied by pouring glaze, and its specific gravity is 1.34g / cm 3 , glaze application amount is 750g / m 2 .
[0052] Step 4: Place the bricks coated with silver sand metal dry granule glaze into the kiln for firing. The firing ring temperature is 1185°C and the firing time is 45 minutes.
[0053] Step 5. Fine polishing, edge grinding, classification and packaging. Install 6 sets of grinding brushes for fine polishing.
[0054] Figure 1 1 is a brick surface effect diagram of the porcelain brick of Example 1. Figure 1 It can be seen that the surface of the porcelain tile sample has a silver sand effect. Moreover, the porcelain tile sample prepared in Example 1 has a delicate feel. The National Ceramic and Plumbing Sanitary Ware Product Quality Inspection and Testing Center has measured that the pollution resistance is level 5, the wear resistance is level 4 at 6000 revolutions, and the water absorption rate of the ceramic tile after firing is within 0.5wt%.
[0055] Example 2
[0056] The preparation method of the wear-resistant porcelain tile with silver sand effect on the surface comprises the following steps:
[0057] Step 1: Press the green body powder into shape to obtain a brick.
[0058] Step 2. Apply silver sand glaze on the surface of the dried brick. The mineral composition of the silver sand glaze includes zirconium-free glaze and cobalt black material, wherein the mass ratio of zirconium-free glaze to cobalt black material is 100:4. The chemical composition of the zirconium-free glaze includes: by mass percentage, loss on ignition: 1.5%; SiO 2 :58.5%;Al 2 O 3 :30.2%; CaO: 0.7%; MgO: 0.4%; K 2 O: 4.4%; Na 2 O: 4.3%. The mineral composition of the zirconium-free glaze includes: by mass percentage, potassium feldspar 40%, sodium feldspar 5%, nepheline 25%, washed kaolin 9%, quartz 6%, calcined alumina 15%. The chemical composition of the silver sand glaze includes: by mass percentage, ignition loss: 1.5%; SiO2 :55.6%;Al 2 O 3 :29.8%; CaO: 0.8%; MgO: 0.3%; K 2 O: 3.6%; Na 2 O: 4.6%; CoO: 3.8%. The silver sand glaze is applied by pouring glaze, with a specific gravity of 1.84g / cm 3 , glaze application amount is 650g / m 2 .
[0059] Step 3. Apply silver sand metal dry granule glaze on the surface of the brick after applying the silver sand glaze. The mineral composition of the silver sand metal dry granule glaze includes flaky mica iron oxide and silver sand metal dry granules, wherein the mass ratio of flaky mica iron oxide to silver sand metal dry granules is 10:90. The chemical composition of the flaky mica iron oxide includes: by mass percentage, Fe 2 O 3 :99.45%;SiO 2 :0.55%. The diameter-to-thickness ratio of the flaky mica iron oxide is 80. The chemical composition of the silver sand metal dry particles includes: by mass percentage, ignition loss: 0.6%; Al 2 O 3 :14.2%;SiO 2 :41.3%;Fe 2 O 3 :16.8%; CaO: 2.4%; MgO: 0.2%; K 2 O: 3.1%; Na 2 O: 2.4%; TiO 2 :3.2%;ZnO:2.8%;P 2 O 5 :7.8%;Li 2 O: 2.5%; CaF 2 :2.7%. The mineral composition of the silver sand metal dry particles includes: by mass percentage, potassium feldspar 20%, washed kaolin 10%, quartz 20%, iron phosphate 30%, fluorite 6%, zinc oxide 4%, spodumene 6%, rutile 4%. The chemical composition of the silver sand metal dry particle glaze includes: by mass percentage, ignition loss: 0.6%; Al 2 O 3 :12.4%;SiO 2 :36.8%;Fe 2 O 3 :25.8%; CaO: 2.1%; MgO: 0.2%; K 2 O: 2.8%; Na 2 O: 2.2%; TiO 2 :2.8%;ZnO:2.5%;P2 O 5 :7.1%;Li 2 O: 2.3%; CaF 2 :2.4%. Silver sand metal dry granular glaze is applied by pouring glaze, and its specific gravity is 1.34g / cm 3 , glaze application amount is 850g / m 2 .
[0060] Step 4: Put the bricks with silver sand metal dry granule glaze into the kiln for firing. The firing temperature is 1180℃ and the firing time is 45 minutes.
[0061] Step 5. Fine polishing, edge grinding, classification and packaging. Install 6 sets of grinding brushes for fine polishing.
[0062] Figure 2 2 is a brick surface effect diagram of the porcelain brick of Example 2. Figure 2 It can be seen that the surface of the porcelain tile sample has a silver sand effect. Moreover, the porcelain tile sample prepared in Example 2 has a delicate feel.
[0063] Comparative Example 1
[0064] The method is basically the same as Example 1, except that in step 2, a zirconium-free glaze is used instead of a silver sand glaze. The chemical composition of the zirconium-free glaze includes: by mass percentage, loss on burning: 1.8%; SiO 2 :57.7%;Al 2 O 3 :31.2%; CaO: 0.8%; MgO: 0.3%; K 2 O: 3.4%; Na 2 O: 4.8%. The zirconium-free glaze is applied by pouring glaze, with a specific gravity of 1.84g / cm 3 , glaze application amount is 650g / m 2 .
[0065] The zirconium-free glaze of comparative example 1 has no cobalt black material added, and the entire glaze surface is bluish-yellow, unable to reflect the silver sand effect, resulting in only sporadic flashing effects on the tile surface.
[0066] Comparative Example 2
[0067] It is basically the same as Example 1, with the main difference being that in step 3, the flaky mica iron oxide in the silver sand metal dry granular glaze is replaced with granular mica iron oxide, whose diameter-to-thickness ratio is 40.
[0068] The silver metallic luster of the granular mica iron oxide in Comparative Example 2 is weak. When added into the silver sand metal dry particle glaze, the silver sand effect of the glaze surface is poor after firing.
[0069] Comparative Example 3
[0070] It is basically the same as Example 1, the main difference is that the specific gravity of the silver sand metal dry particle glaze is 1.32g / cm 3 , glaze application amount is 600g / m 2 .
[0071] The amount of the silver sand metal dry particle glaze applied in Comparative Example 3 is too small, and crystallization of the glaze surface is difficult, resulting in a weak silver sand effect on the surface of the prepared porcelain tile sample.
[0072] Comparative Example 4
[0073] It is basically the same as Example 1, the main difference is that the specific gravity of the silver sand metal dry particle glaze is 1.34g / cm 3 , glaze application amount is 900g / m 2 .
[0074] The amount of silver sand metal dry granular glaze applied in Comparative Example 4 is too much, resulting in the prepared porcelain tile sample being too turtle-shaped, the tile surface being arched, and increasing the production cost.
[0075] Comparative Example 5
[0076] It is basically the same as Example 1, with the main difference being that the maximum sintering temperature is 1170°C.
[0077] The firing temperature of Comparative Example 5 is too low. Although the surface of the tile has a silver sand effect, the surface is rough and the pollution resistance is poor.
[0078] Comparative Example 6
[0079] It is basically the same as Example 1, with the main difference being that the maximum sintering temperature is 1210°C.
[0080] The firing temperature of Comparative Example 6 is too high, and since the silver sand metal dry particles cannot be crystallized, the surface silver sand effect is poor.
[0081] Comparative Example 7
[0082] It is basically the same as Example 1, with the main difference being:
[0083] Step 2. The mineral composition of the silver sand glaze includes zirconium-containing glaze and cobalt black material, wherein the mass ratio of zirconium-containing glaze to cobalt black material is 100:3. The chemical composition of the zirconium-containing glaze includes: by mass percentage, ignition loss: 1.8%; SiO 2 :54.8%;Al 2 O 3 :29.6%; CaO: 0.7%; MgO: 0.3%; K 2 O: 3.2%; Na 2O: 4.5%; ZrO: 5.1%. The mineral composition of the zirconium-containing glaze includes: by mass percentage, potassium feldspar 37%, sodium feldspar 4.5%, nepheline 23%, washed kaolin 8%, quartz 5.5%, calcined alumina 13.5%, zirconium silicate 8.5%. The chemical composition of the silver sand glaze includes: by mass percentage, ignition loss: 1.8%; SiO 2 :53.2%;Al 2 O 3 :28.7%; CaO: 0.7%; MgO: 0.3%; K 2 O: 3.1%; Na 2 O: 4.3%; ZrO 2 : 5.0%; CoO: 2.9%. The silver sand glaze is applied by pouring glaze, and the specific gravity is 1.84g / cm 3 , glaze application amount is 650g / m 2 .
[0084] The silver sand glaze of Comparative Example 7 contains zirconium and has a high whiteness. More cobalt black material needs to be added to achieve the silver sand effect of zirconium-free glaze, which increases production costs and the silver sand effect is relatively poor.
[0085] Comparative Example 8
[0086] It is basically the same as Example 1, with the main difference being:
[0087] Step 3. Mix the silver sand metal dry particles and the transparent polishing glaze to form the silver sand polishing glaze. The chemical composition of the silver sand metal dry particles includes: by mass percentage, ignition loss: 0.6%; Al 2 O 3 :14.2%;SiO 2 :41.3%;Fe 2 O 3 :16.8%; CaO: 2.4%; MgO: 0.2%; K 2 O: 3.1%; Na 2 O: 2.4%; TiO 2 :3.2%;ZnO:2.8%;P 2 O 5 :7.8%;Li 2 O: 2.5%; CaF 2 :2.7%. The mineral composition of the silver sand metal dry particles includes: by mass percentage, potassium feldspar 20%, washed kaolin 10%, quartz 20%, iron phosphate 30%, fluorite 6%, zinc oxide 4%, spodumene 6%, rutile 4%. The chemical composition of the transparent polishing glaze includes: by mass percentage, ignition loss: 8.6%; SiO 2 :48.6%;Al 2 O3 :13.2%; CaO: 6.8%; MgO: 3.4%; K 2 O: 3.8%; Na 2 O: 2.6%; BaO: 8.5%, ZnO: 4.5%. Apply silver sand polishing glaze on the surface of the brick after applying silver sand glaze. The silver sand polishing glaze is applied by pouring glaze, and the specific gravity is 1.84g / cm 3 , glaze application amount is 650g / m 2 .
[0088] Comparative Example 8: Silver sand metal dry particles and transparent polishing glaze were mixed and poured on the brick surface after silver sand glaze was applied. After firing, the glaze surface had many pores. The wear resistance was tested by the National Ceramic and Plumbing Sanitary Ware Product Quality Inspection and Testing Center as level 3 1500 revolutions.
Claims
1. A method for preparing a wear-resistant porcelain tile having a silver sand effect on the surface, characterized in that: The preparation method comprises the following steps: Apply silver sand glaze on the surface of the brick; Applying silver sand metal dry granular glaze on the surface of the brick after applying the silver sand surface glaze; The brick blanks applied with the silver sand metal dry granular glaze are fired and polished to obtain wear-resistant porcelain tiles with a silver sand effect on the surface.
2. The preparation method according to claim 1, characterized in that: The mineral composition of the silver sand metal dry particle glaze includes flaky mica iron oxide and silver sand metal dry particles; wherein the mass ratio of the flaky mica iron oxide to the silver sand metal dry particles is (5-10):(90-95).
3. The preparation method according to claim 2, characterized in that: The chemical composition of the silver sand metal dry particles includes: by mass percentage, ignition loss: 0.5% to 0.8%; Al2O3: 14.2% to 18.5%; SiO2: 40.1% to 49.3%; Fe2O3: 10.4% to 19.6%; CaO: 1.2% to 4.3%; MgO: 0.05% to 0.5%; K2O: 1.2% to 4.4%; Na2O: 1.6% to 3.8%; TiO2: 2.5% to 4.5%; ZnO: 2.4% to 4.8%; P2O5: 7.2% to 14.2%; Li2O: 1.4% to 3.6%; CaF2: 2.1% to 4.3%.
4. The preparation method according to claim 2 or 3, characterized in that: The diameter-to-thickness ratio of the flaky mica iron oxide is 65-110.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The chemical composition of the silver sand metal dry particle glaze includes: by mass percentage, loss on ignition: 0.6% to 1.0%; Al2O3: 12.3% to 16.2%; SiO2: 36.2% to 46.6%; Fe2O3: 15.7% to 25.9%; CaO: 1.2% to 3.6%; MgO: 0.05% to 0.5%; K2O: 1.4% to 3.2%; Na2O: 1.3% to 2.8%; TiO2: 1.9% to 4.1%; ZnO: 2.1% to 4.2%; P2O5: 6.5% to 12.5%; Li2O: 1.2% to 3.4%; CaF2: 1.8% to 3.9%.
6. The preparation method according to any one of claims 1 to 5, characterized in that The silver sand metal dry granule glaze is applied by pouring glaze; preferably, the specific gravity of the silver sand metal dry granule glaze is 1.30-1.34 g / cm 3 , glaze application amount is 750~860g / m 2 .
7. The preparation method according to any one of claims 2 to 6, characterized in that The mineral composition of the silver sand metal dry particles includes, by mass percentage, 20% to 30% potassium feldspar, 10% to 20% washed kaolin, 20% to 30% quartz, 20% to 40% iron phosphate, 5% to 10% fluorite, 4% to 10% zinc oxide, 6% to 8% spodumene, and 4% to 6% rutile.
8. The preparation method according to any one of claims 1 to 7, characterized in that The mineral composition of the silver sand glaze includes zirconium-free glaze and cobalt black material, wherein the mass ratio of the zirconium-free glaze to the cobalt black material is 100:(2-5).
9. The preparation method according to claim 8, characterized in that: The chemical composition of the zirconium-free glaze includes, by mass percentage, loss on ignition: 1.2% to 1.8%; SiO2: 56.4% to 60.6%; Al2O3: 28.2% to 32.3%; CaO: 0.6% to 0.9%; MgO: 0.3% to 0.5%; K2O: 3.1% to 5.2%; Na2O: 3.2% to 4.8%; Preferably, the mineral composition of the zirconium-free glaze includes, by mass percentage, 35% to 45% potassium feldspar, 0.1% to 5% sodium feldspar, 20% to 35% nepheline, 8% to 12% washed kaolin, 5% to 10% quartz, and 15% to 20% calcined alumina.
10. The preparation method according to any one of claims 1 to 9, characterized in that: The chemical composition of the silver sand glaze includes: by mass percentage, loss on ignition: 1.4% to 2.2%; SiO2: 55.4% to 62.3%; Al2O3: 27.8% to 31.5%; CaO: 0.6% to 1.0%; MgO: 0.2% to 0.4%; K2O: 3.2% to 5.7%; Na2O: 3.2% to 5.8%; CoO: 2.5% to 4%.
11. The preparation method according to any one of claims 1 to 10, characterized in that: The silver sand glaze is applied by pouring glaze; preferably, the specific gravity of the silver sand glaze is 1.82-1.86 g / cm 3 , glaze application amount is 600~700g / m 2 .
12. The preparation method according to any one of claims 1 to 11, characterized in that: The maximum firing temperature is 1180-1200°C, and the firing time is 40-50 minutes.
13. A wear-resistant porcelain tile with a silver sand effect on the surface, characterized in that: The wear-resistant porcelain tile having a silver sand effect on the surface is obtained according to the preparation method described in any one of claims 1 to 12.
Citation Information
Patent Citations
Production process of ceramic tile with high-light and matte precious metal gloss
CN106810297A
Metal dry granular glaze, metallic luster ceramic tile and preparation method of metallic luster ceramic tile
CN111847877A
Ceramic tile with silver metal texture and preparation method thereof
CN112125525A
Low-temperature frit for matt ceramic glaze and preparation process for preparing matt glaze ceramic product by using low-temperature frit
CN112340995A
Pearlescent dry particles, pearlescent glazed tile and preparation method thereof
CN114195386A